Decreased class size, increased active learning? Intended and enacted teaching strategies in smaller classes. (March 2019) - Wright, Mary C; Bergom, Inger; Bartholomew, Tracy
Small class size is often used as an indicator of quality in higher education, and some research suggests that instructors in smaller classes more often use activities that are learner-centered and that involve physical and mental activity on the part of learners, such as group work, simulations, and case studies. However, we have little information on how instructors change their pedagogical practice when they teach in large- versus small-class settings. In this study, we examine alignment between intended and enacted teaching strategies, or initial plans and specific ways in which instructors reported altering their teaching in the context of a university policy shift to smaller classes. Furthermore, we examine instructional challenges in this shift to call attention to professional development needs of small-class teaching and to best leverage the benefits of such activities for student performance and retention.